PROVERBS AND IDIOMS IN ENGLISH AND UZBEK: A COMPARATIVE ANALYSIS (MULTIDISCIPLINARY JOURNAL: FUNDAMENTAL RESEARCH SCIENTIFIC JOURNAL, 2025)
This article examines English and Uzbek proverbs and idioms from a comparative perspective, focusing on their semantic structures, cultural backgrounds, and functional roles in everyday communication. Proverbs and idioms, as carriers of national wisdom and collective experience, reflect the values, traditions, and worldview of a society. By analyzing similarities and differences in imagery, metaphorical meanings, and pragmatic usage, the study highlights how universal human concepts such as love, friendship, work, and morality are expressed through language. The findings reveal that while many proverbs and idioms share common themes due to universal human experiences, their linguistic forms and cultural associations often remain unique to each language.